VARIATIONS OF DEMONSTRATION LEARNING MODEL IN EXPRESSING IMAGES IN DETAIL USING DIRECT PRACTICE METHOD IN EARLY CHILDHOOD - Amalia, Sri Rezeki; Darmiyati, Darmiyati (Journal of K6, Education and Management, 2018)
This study aims to find the activity of teachers and children as well as the result of fine motor development of children in expressing themselves through the detail drawing movement by applying demonstration model combined with example non-example model and direct practice method. This study used qualitative approach and classroom action research (car) with qualitative and quantitative analysis method that was conducted by three times, the research subject was teachers and children, and the data was collected through observation and interview. This research consisted of the following steps: planning, implementation, observation, and reflection. This research was. The results show that the fine motor development of children increase after the observation was conducted on teachers who implement learning and in children who follow the learning drawing in detail.